Investigation of the levitation force of field-cooled YBCO and MgB2 disks as functions of temperature. (16th May 2017) - Bernstein, P; Colson, L; Dupont, L; Noudem, J
Abstract: We report levitation force cycles resulting from measurements carried out on a YBCO and a MgB2 disk cooled down in the field of a permanent magnet. In both cases the amplitude of the levitation force tends toward maximum values as the temperature decreases. Otherwise, the cycles are almost closed at low temperature and strongly hysteretic in the high temperature range. The hysteresis of the force cycles is attributed to the distribution of the currents induced in the sample by the field of the magnet. The saturation of the levitation forces at low temperature is related to that of the magnetic moment of the disks. We show that this type of measurement allows for the determination of the critical current density of superconductors in a restricted domain of temperatures.